Analysis of Islamic Values in Scout Activities for Shaping the Pancasila Student Profile - Handayani, Tati; Tanjung, Ellisa Fitri; Nurzannah, Nurzannah (Lectura : Jurnal Pendidikan, 2025)
Scouting extracurricular activities serve as a platform for character development, particularly in integrating Islamic values into students’ daily lives. This study aims to analyze how Islamic values are embedded in scouting activities at MTsN Serdang Bedagai and their role in shaping the Pancasila Student Profile. Using a qualitative approach with a descriptive-analytical method, data were collected through observations, interviews, and document analysis. Key informants included the head of the madrasah, scout trainer teachers, and students actively participating in scouting. The data analysis process involved reduction, presentation, and conclusion drawing techniques. The findings indicate that scouting activities significantly contribute to the internalization of Islamic values, such as faith, discipline, leadership, responsibility, and cooperation. Additionally, scouting programs emphasize knowledge acquisition based on scouting principles, technical proficiency in drills like Kolone Tongkat, and mindset formation guided by the Dasa Darma Pramuka (Scout Code). Students are encouraged to apply Islamic teachings through discipline, respect, self-confidence, and fairness, aligning with the principles of the Pancasila Student Profile. To enhance the integration of Islamic values, this study suggests strengthening Islamic based scouting curricula, improving mentoring for instructors, and incorporating structured religious guidance in scouting sessions. Furthermore, integrating community engagement and utilizing digital platforms can enhance character development. These findings contribute to discussions on Islamic character education and provide insights for madrasahs seeking to implement extracurricular activities as a means of fostering holistic student development.